Kandungan Gizi dan Organoleptik Biskuit dengan Subtitusi Tepung Sukun dan Stevia - Muhlishoh, Arwin; Aryanti Setyaningsih; Zuhria Ismawanti (JURNAL GIZI DAN KESEHATAN, 2021)
Breadfruit flour is a local food ingredient that can be used as a substitute for flour with a low glycemic index content, as well as high levels of starch, amylose and resistant starch. While stevia is a source of natural sweeteners with a sweetness level of 200-300 times sweeter than cane sugar. Both ingredients are safe for patients with diabetes mellitus. This study was conducted to evaluate the nutritional and organoleptic content of biscuits substituted with breadfruit and stevia flour. Nutritional content was carried out by proximate test. Meanwhile, the organeleptic test was carried out by the hedonic test. The study was conducted using a completely randomized design with four proportion factors adding 15-50% breadfruit flour, while 8 grams of stevia was added. There was a significant difference in the average organoleptic test for each treatment of breadfruit flour and stevia biscuit formulations (p<0.05). From the results of the different test using Tukey HSD, it is known that the respondents "rather like" the taste, aroma, texture and appearance of the F1 biscuit formulation which is statistically the same as the F0 biscuit formulation (control) (p> 0.05). There was no significant difference in the average chemical quality test (moisture, ash, protein, fat, carbohydrate, and crude fiber content) in each treatment group of breadfruit flour and stevia biscuit formulations (p>0.05). Biscuit F1 is the product of choice in the manufacture of biscuits substituted with breadfruit flour and stevia with nutritional and organoleptic content close to the control. ABSTRAK Tepung sukun merupakan bahan pangan lokal yang dapat digunakan sebagai pengganti terigu dengan kandungan indeks glikemik rendah, serta kadar pati, amilosa dan pati resisten yang tinggi. Sedangkan stevia adalah sumber bahan pemanis alami dengan tingkat kemanisan 200-300 kali lebih manis dari pada gula tebu. Kedua bahan tersebut aman untuk pasien diabetes mellitus. Penelitian ini dilakukan untuk mengevaluasi kandungan gizi dan organoleptik pada biskuit yang disubtitusi tepung sukun dan stevia. Kandungan gizi dilakukan dengan uji proksimat. Sedangkan uji organeleptik dilakukan dengan uji hedonik. Penelitian dilakukan menggunakan Rancangan Acak Lengkap dengan empat faktor proposi penambahan tepung sukunsebanyak 15 â€“ 50%, sedangkan stevia ditambahkan sebesar 8 gram. Terdapat perbedaan yang signifikan rata-rata uji organoleptik pada tiap perlakuan formulasi biskuit tepung sukun dan stevia (p<0,05). Dari hasil uji beda menggunakan Tukey HSD, diketahui bahwa responden â€œagak sukaâ€ terhadap rasa, aroma, tekstur dan kenampakan formulasi biskuit F1 yang secara statistik sama dengan formulasi biskuit F0 (kontrol) (p>0,05). Tidak terdapat perbedaan yang signifikan rata-rata uji mutu kimia (kadar air, abu, protein, lemak, karbohidrat, dan serat kasar) pada tiap kelompok perlakuan formulasi biskuit tepung sukun dan stevia (p>0,05). Biskuit F1 merupakan produk terpilih pada pembuatan biskuit subtitusi tepung sukun dan stevia dengan kandungan gizi dan organoleptik mendekati kontrol.